A percepção dos estudantes sobre a formação na universidade : uma análise por meio do questionário do estudante do ENADE - Merlo, Tatiane (2018)
The present research consists of a study of the evaluation of higher education, made by the students, with a focus on the the National Exam of Students’ Performance (ENADE). In order to ascertain the students’ satisfaction regarding matters related to the course and the Institution, the National Institute of Studies and Educational Researches Anísio Teixeira (INEP) makes use of the ENADE’s Student Questionnaire, one of the tools of the National System for the Evaluation of Higher Education (SINAES). Bearing this in mind, the guiding questions for this research are: What is the students’ perception of the formation in the Institution? Do the coordinators utilize these data I order to propose actions to be taken in the management of the courses? In order to answer these questions, two sources of data were considered: answers to the Student Questionnaire given by the students graduating in 2014 from the North University Center of Espírito Santo (CEUNES); and interview made with the coordinators of these courses in order to get to know their actions regarding the information generated by the Questionnaire. The research is characterized as being descriptive with a quantitative-qualitative approach and, regarding data collection, it is a Case Study and Bibliographical Research. The results demonstrate that the graduates of the CEUNES’ courses that were investigated are satisfied with the contribution of their course in their academic, professional and personal formation. The only exception is the Physics course, which presented fragility in almost every matter analyzed. The results also indicate that all the coordinators interviewed acknowledge the importance of the evaluation of higher education made by the students, however, most of them never made use of these data information in order to develop improvements. Accordingly, it can be inferred that the Institution does not standardize the usage of these data, since each coordination uses them (or not), according to their own interest. Therefore, it is suggested to the studied Institution the implementation of a seminar on the importance of the Student Questionnaire’s data. The delivering of this seminar will allow the academic community having direct contact with the University’s Internal Evaluation Commission (CPA) for query solution, since one of the coordinators’ complaints is due to the lack of support from this Commission in the evaluation processes. It is also intended, through this seminar, to organize work groups to initiate the discussion on the evaluations, as well as reflecting on actions that can be taken in the Institution, being one of them the possibility to develop a poll with the students in order to ascertain the reasons that generate dissatisfaction. For sure, the Institution will be able to gather information so as to subsidize actions that will cooperate towards the improvement of the courses’ quality and, as a result, the student satisfaction